Incident atrial fibrillation and heart failure in treated hypertensive patients with left ventricular hypertrophy. The LIFE Study - Casper N. Bang; Anders M. Greve; Lars Køber; Anujan Muthiah; Sverre E. Kjeldsen; Stevo Julius; Kristian Wachtell; Richard B. Devereux; Peter M. Okin (Open Exploration Publishing Inc., 2022)
Aim: The present study investigated the appearance and severity of atrial fibrillation (AF) and heart failure (HF) in 8,702 hypertensive patients with left ventricular hypertrophy (LVH) receiving antihypertensive treatment in a prospective trial. Methods: Patients who had a history of AF or HF were not included, and the participants had sinus rhythm when they were randomly allocated to blinded study medication. Endpoints were adjudicated. Results: Incident AF occurred in 679 patients (7.8%) and HF in 246 patients (2.8%) during 4.7 ± 1.1 years mean follow-up. Incident AF was associated with a > 4-fold increased risk of developing subsequent HF [hazards ratios (HRs) = 4.7; 95% confidence intervals (CIs), 3.1-7.0; P < 0.001] in multivariable Cox analyses adjusting for age, sex, race, randomized treatment, standard cardiovascular risk factors and incident myocardial infarction. The development of HF as a time-dependent variable was associated with a multivariable-adjusted 3-fold increase of the primary study endpoint (HRs = 3.11; 95% CIs, 1.52-6.39; P < 0.001) which was a composite of myocardial infarction, stroke or cardiovascular death. Incident HF was associated with a > 3-fold increased risk of developing subsequent AF (HRs = 3.3; 95% CIs, 2.3-4.9; P < 0.001). This development of AF was associated with a > 2-fold increase of the composite primary study endpoint in multivariable Cox analysis (HRs = 2.26; 95% CIs, 1.09-4.67; P = 0.028). Conclusions: Incident atrial fibrillation and heart failure are associated with increased risk of the other in treated hypertensive patients with left ventricular hypertrophy. Such high-risk hypertensive patients who subsequently develop both atrial fibrillation and heart failure have particular high risk of composite myocardial infarction, stroke or cardiovascular death (ClinicalTrials.gov identifier: NCT00338260).